Pengaruh Penambahan Ekstrak Bawang Putih dan Cabai pada Telur Asin Itik Terhadap Kandungan Protein, Total Mikroba, dan Tingkat Kesukaan Konsumen - Sumarsih; Athiefah Fauziyyah (Food Scientia : Journal of Food Science and Technology, 2021)
This study is aimed to determine the effect of garlic and chili extracts additiontowards the protein content, total microbial count and consumer hedonic level ofsalted duck eggs. This study was conducted using Completely Randomized Design(CRD) with 3 treatments and repeated three times. The treatments tested were theaddition of 100% garlic extract and 50% garlic: 50% chili with subsequent 7 daysripening and 3 days incubation period. The parameters observed were proteincontent, total microbial count and consumer hedonic level. The data was statisticallyanalyzed using analysis of variance (ANOVA) with 5% significance level and furtherprocessed with Duncan's Multiple Range Test (DMRT) for those significantlydifferent treatments. The results shows that the addition of 50% garlic and 50% chiliextracts followed by 7 days ripening and 3 days incubation exhibit an elevatedprotein content on the salted duck eggs without any significant effect on its physicalappearance, color, texture as well as the total microbial count.